Dynamic Modelling of Battery Cooling Systems for Automotive Applications - Hasselby, Fabian (My University, 2014)
The automotive industry is currently undergoing a period of historic upheaval. Under mounting pressure from increasing fuel costs and emission legislations, the industry now faces numerous challenges wherein the reduction of consumed energy and emission mitigation become principal. In light of these circumstances the hybrid electric vehicle technology is emerging. With its aptitude for combining the benefits of both the internal combustion engine and those of the electrical vehicle, the hybrid electrical vehicle is presently becoming more of a viable option. Any further improvement done to enhance the range and performance of the vehicle does, however, come at a cost. Frequent charge- and discharge cycles lead to residual heat build-up within the cells and will, if left unchecked, causes increased cell degradation, which in turn decreases the lifetime of the cells as well as battery performance. Consequently, finding methods for cooling these cells to their preferred temperature range becomes essential. In this thesis work a One Dimensional Computational Fluid Dynamics (1D CFD) modelling approach was taken in order to construct and evaluate a model of a hybrid electric vehicle’s battery thermal management system. The study showed that it is possible to build a complete model of such a system capable of producing accurate predictions with only slight deviations from actual measurements. The benefits of using such models early on in the vehicle development stages was also exemplified by using the model to conceive a possible control scheme for cooling the battery in an energy efficient manner. The findings from this study revealed that designing an energy efficient method of controlling the system is a difficult endeavour, not only because of the many constraints placed on an actual system, as well as, it’s dynamic behaviour, but also due to the way one chooses to measure efficiency improvements. It is likely that a more comprehensive analysis would yield other and better control strategies than the example demonstrated in this thesis work.
Keywords: Energi; Hållbar utveckling; Termisk energiteknik; Energy; Sustainable Development; Thermal energy engineering